1987
DOI: 10.1007/bf00290098
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and linkage relationships of glutamate oxaloacetate transaminase isoenzymes in apple

Abstract: Four zones of enzymatic activity for glutamate oxaloacetate transaminase (GOT) were found in apple tissue. A dimeric gene, GOT-1, determining the fastest migrating zone, was identified. Six alleles were found, including a near null allelle which produced detectable heterodimeric bands but not homodimeric bands. A marked deficit or absence of certain geno-types in all backcrosses and in some crosses between unrelated varieties was attributed to the close linkage (r=0.02±0.005) of GOT-1 with the incompatibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Based on data on crossincompatibility between cultivars, scored by the inhibition of pollen tube growth in the style, he attributed an S genotype to a number of cultivars, most of which are not of commercial importance nowadays [25]. Manganaris and Alston [29] observed a phenotypic linkage of the S locus with the iso-enzyme gene glutamate oxaloacetate transaminase (GOT)-1, and deduced the S genotype of a few apple cultivars (not including Golden Delicious). Speranza and Calzoni [37] studied the effect of apple style protein fractions on in vitro pollen development; it was shown that some crude protein fractions, including a fraction containing a 30 kDa glycoprotein not found in other fractions, appeared to contain specific inhibitors of self-pollen tube growth.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data on crossincompatibility between cultivars, scored by the inhibition of pollen tube growth in the style, he attributed an S genotype to a number of cultivars, most of which are not of commercial importance nowadays [25]. Manganaris and Alston [29] observed a phenotypic linkage of the S locus with the iso-enzyme gene glutamate oxaloacetate transaminase (GOT)-1, and deduced the S genotype of a few apple cultivars (not including Golden Delicious). Speranza and Calzoni [37] studied the effect of apple style protein fractions on in vitro pollen development; it was shown that some crude protein fractions, including a fraction containing a 30 kDa glycoprotein not found in other fractions, appeared to contain specific inhibitors of self-pollen tube growth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a genetic marker can identify dwarf Malus clones early in their growth (Zhang and Tang 1987). Another isozyme marker in apple has been found tightly linked to the S gene(s) governing incompatibility (Manganaris and Alston 1987). Under certain conditions, nucellar seedlings in Citrus L. spp.…”
Section: Exploiting Associations Among Traits Of Interest and Geneticmentioning
confidence: 99%
“…Similarly, three loci control GOT isozymes were reported in citrus (Hirai and Kajiura, 1987), carrot (Westphal and Wricke, 1989) and Populas maximowiczii (Rajora, 1986). The occurrence of null GOT alleles has been reported in citrus at Got-3 (Hirai and Kajiura, 1987), potato at Got-2 (Oliver and Martinez-Zapater, 1985), and apple at Got-1 and Got-2 (Manganaris and Alston, 1987). …”
Section: Discussionmentioning
confidence: 98%